Informatization Features Of Surgical Units Of A Medical Organization (Journal of Pharmaceutical Negative Results, 2023)
The abundance of diagnostic information obliges the attending physician to accumulate knowledge, constantly improve in related disciplines, and understand representatives of other specialities involved in the therapeutic diagnostic process and the formation of a diagnosis.The introduction of automated control systems (ACS) is a real lever for improving the quality of medical care, intensifying personnel work, and improving the medical and diagnostic process. Improving the activities and quality of the organization of surgical care will allow the management bodies to provide timely, reliable and comprehensive information necessary for an in-depth and focused analysis of the work of hospital departments.